Resposta imune à infecção por Mycobacterium bovis em linhagens de camundongos geneticamente selecionados (Seleção IV-A) - Cavalheiro, Juliana Semim [UNESP] (Universidade Estadual Paulista (Unesp), 2003)
A tuberculose bovina é uma doença transmissível de natureza granulomatosa crônica e caráter progressivo, apresentando tubérculos característicos, tendo como agente etiológico o Mycobacterium bovis - um patógeno intracelular. A imunidade celular é o mecanismo mais efetivo para o controle da infecção por Mycobacterium spp. Esta resposta resulta no acúmulo de fagócitos e na formação de lesão macroscópica (tubérculo ou granuloma tuberculoso), na tentativa de impedir a proliferação e disseminação bacteriana. Neste trabalho foram utilizados modelos experimentais murinos, obtidos por seleção genética bidirecional de camundongos bons (High=H) e maus (Low=L) produtores de anticorpos (Seleção IVA) contra antígenos naturais complexos. Trabalhos anteriores demonstraram alterações funcionais de células imunocompetentes, particularmente de macrófagos, sugerindo que os animais HIV-A seriam mais susceptíveis à infecção causada por patógenos intracelulares, enquanto que ocorreria maior susceptibilidade dos LIV-A à infecção por patógenos extracelulares, quando a imunidade humoral seria o mecanismo mais importante... .

The bovine tuberculosis is a transmissible disease, showing a chronic and progressive character, with typic tubercles. Its etiological agent, Mycobacterium bovis, is an intracellular pathogen. Cell-mediated immunity is the most effective mechanism for this infection control, with phagocytes accumulum and formation of a macroscopic lesion, aiming to avoid the bacteria proliferation and dissemination. In this work, a murine experimental model was used, with mice genetically selected for high (H) and low (L) antibody production (Selection IV-A). Previous works related functional alterations in immunecompetent cells, manily macrophages, suggesting that HIV-A mice were more susceptible to intracellular pathogens, whereas LIV-A were more susceptible to extracellular ones, when humoral-mediated immunity would be the most important mechanism. The goal of this work was to evaluate the macrophagic activity and to characterize the immune response of Mycobacterium bovis-AN5-infected mice. The response prolife previously observed in these strains was not similar in the Mycobacterium bovis infection; however, it was in agreement with works carried out with selection I, which is very similar the selection IV-A with regards to infection with Mycobacterium tuberculosis and Bacillus Calmette-Guérin. As to the bacterial recovery, LIV-A selection showed a higher containnment of the infectious process in the lung, but not in the spleen, where HIV-A selection was more resistant. With respect the macrophagic activity, H2O2 seemed to be not involved in the containment of the infection in both strains, since there was an inibition of this metabolite generation. NO and TNF- production was also analysed, and seemed to be important in the control of bacterial replication, varying according to the strain, time period and compartiment. Antibody production was also evaluated... (Complete abstract, click electronic address below).
Keywords: Resposta imune; Imunologia veterinaria; Immunologicals Aspects; Experimental Studies; Mycobacterium bovis